2013
DOI: 10.1371/journal.pone.0075088
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Recurrence Risk in Relation to the Use of Lipid-Lowering Drugs in a Prospective Breast Cancer Patient Cohort

Abstract: Lipid-lowering drugs are used for the prevention of cardiovascular diseases. Statins are the most commonly used lipid-lowering drugs. Evidence from preclinical and observational studies suggests that statins might improve the prognosis of breast cancer patients. We analyzed data from the German MARIEplus study, a large prospective population-based cohort of patients aged 50 and older, who were diagnosed with breast cancer between 2001 and 2005. For overall mortality, breast-cancer specific mortality, and non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 22 publications
(24 reference statements)
9
53
0
Order By: Relevance
“…Interestingly, in a study of 18,769 patients, benefit was observed only among females with ER-positive breast cancer, 26 in agreement with our results. Similarly, large population-based studies of patients with stage I-III breast cancer receiving lipidlowering regimens including statins confirmed a decreased risk of recurrence, 30 as well as lower overall cancer and breast cancer-specific mortality among statin users. 25 Studies suggest that the "statin effect" was stronger in tumors that were positive for hormone receptors.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, in a study of 18,769 patients, benefit was observed only among females with ER-positive breast cancer, 26 in agreement with our results. Similarly, large population-based studies of patients with stage I-III breast cancer receiving lipidlowering regimens including statins confirmed a decreased risk of recurrence, 30 as well as lower overall cancer and breast cancer-specific mortality among statin users. 25 Studies suggest that the "statin effect" was stronger in tumors that were positive for hormone receptors.…”
Section: Discussionmentioning
confidence: 83%
“…This finding is consistent with virtually all previously reported data (cancer-specific mortality: HR 0.73, 95% CI 0.59-0.92, P = 0.000; all-cause mortality: HR 0.72, 95% CI 0.58-0.89, P = 0.000). In addition, many articles have confirmed that the use of statins can reduce breast cancer incidence and the risk of recurrence [13,14], thus indicating the wide-ranging protective effects of statins in patients with breast cancer. However, the mechanism for how statins improve the prognosis of patients with cancer differs from that in the cardiovascular field.…”
Section: Discussionmentioning
confidence: 98%
“…Typically, a large body of preclinical data would be backed by numerous replicative observational studies demonstrating consistent associations in different populations. Presently, five observational studies support a protective effect of statins on breast cancer recurrence, 42,43,46,49,50 and these are reinforced by experimental studies of statin effects on breast tumour biomarkers. 36,37 The largest epidemiologic study of the association to date was nested in a nationwide Danish source population, from which more than 18,000 survivors were enrolled and followed for recurrence using the DBCG registry.…”
Section: A Clinical Trial Of Adjuvant Breast Cancer Therapy With Statmentioning
confidence: 92%
“…49 Key limitations of this study—which could readily account for its nearer-null association—include the investigators’ inability to isolate statin exposure from other antilipidaemic exposures, and their inclusion of former users in the unexposed comparison group.…”
Section: Statins and Breast Cancer Prognosismentioning
confidence: 99%